Strengthening presentation skills through TPACK-based canva media for elementary school students - Zahri, Nissa Salsabila; Rahmawati, Fitri Puji (Universitas Ahmad Dahlan, 2024)
The purpose of this study is to describe the enhancement of presentation skills among elementary school students learning Indonesian at SDICT Al Abidin Surakarta through the utilization of TPACK-based Canva media. A descriptive qualitative method was employed in this study. The data consisted of information regarding the use of Canva media for developing presentation skills at SDICT Al-Abidin Surakarta. Observation, interviews, and documentation served as the instruments for data collection. The researchers ensured data validity through credibility checks, diligence, observation, and triangulation. Data analysis techniques involved data reduction, data presentation, and drawing conclusions. The results indicate that students' presentation skills, facilitated by TPACK-based Canva media, have demonstrated proficiency. The integration of TPACK with Canva media has facilitated the meaningful incorporation of technology into learning material. The advantages of employing Canva for enhancing student presentation skills include increased enthusiasm in designing presentation material, boosted student confidence, and opportunities for practicing public speaking skills using material designed and displayed via a projector screen. By incorporating TPACK-based Canva, students can actively participate in designing and presenting information through this media platform.